Reimagining school integration : possibilities for the future - Ayscue, Jennifer B. (Emerald Publishing Limited : IAP | Information Age Publishing, Inc, 2024)
"Since the peak of school desegregation in the late 1980s, schools across the nation have been resegregating such that schools are now as segregated as they were during the 1960s. Segregation is systematically linked to unequal educational opportunities and outcomes while integration, when well structured, is associated with numerous short-term and long-term academic and social benefits for individuals and society. In a time when public education is under attack and our nation is deeply divided along the lines of race, class, and politics, the potential of integration to create more equitable educational opportunities and outcomes for individual students as well as greater social cohesion for our democratic, pluralistic society is more important than ever. Seventy years after the Supreme Court's landmark Brown v. Board of Education decision ruled that segregated schools are inherently unequal, this book reimagines what integration is and could be in our nation's current context of racial and political polarization, the expansion of unregulated choice in public education, and an increasingly diverse, multiracial public school enrollment. Through an exploration of research and policy, this book develops a new conceptualization of integration by describing the contemporary drivers of segregation and recommending strategies to create a more equitable, meaningful, equal-status form of educational integration for the future. This book is a valuable resource for policymakers, scholars, educators, and concerned citizens who are invested in learning about one way to help create a more equitable and just education system"-- Provided by publisher.
Keywords: School integration -- United States.; Education -- Inclusive Education.; Educational strategies and policy: inclusion.; elektronické knihy; electronic books